Pengaruh Disiplin Kerja dan Komunikasi Terhadap Kinerja Karyawan pada CV Cahaya Kartika Raya Tangerang Selatan - Jodi Ananda (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Human resources are a component that cannot be separated from other tools in a company. The data used is primary data by distributing questionnaires in the form of a Google form by sharing links online and techniques using a Likert scale. Testing was carried out on variables X1 (Work Discipline) and X2 (Communication) as the independent variable against Y (Employee Performance) as the dependent variable. The tool used to process data in this research is SPSS version 25 software. This research was conducted in the period April - June 2024. This research is quantitative research. It is known that the Work Discipline variable (X1) on Employee Performance (Y) seen from the coefficients table shows that the tcount value is 6.775, which means tcount > ttable (6.775 > 2.052) with a significance of 0.000 < 0.05. So the hypothesis which states that work discipline partially has a positive and significant effect on employee performance can be accepted. Looking at the Communication variable (X2), it is known that tcount > ttable (3.360 > 2.052) with a significance of 0.002 < 0.05. So the hypothesis which states that communication partially has a positive and significant effect on employee performance can be accepted. It is known that Fcount is 69.981 > Ftable is 3,340 and the significance is 0.000 < 0.05, so it can be concluded that Ho is rejected and Ha is accepted. Work Discipline and Communication variables simultaneously have a significant effect on Employee Performance.